Diabetic Retinopathy Screening In Human Eyes Using Image Processing and Segmentation (International Journal of Innovative Research in Computer Science & Technology, 2020)
Diabetic Retinopathy is a complication in  which the retina of the eye gets damaged due to secretion of  fluid from blood vessels to retina, It may also cause vision  loss. It occurs due to damage of blood vessels in the retina.  In this approach, we suggest an ANN method to detect the  presence of unnatural new blood vessels. This new concept  is used for distinguishing age-related problems i.e., age related macular degeneration (AMD). Our new improved  matched filters distinguishes the higher efficiency in true up  positive feedback and less efficiency in false observation in  previously used filter based on vessel separation. So the aim  is to provide an automated, easy to use, UI based detection  system preparing the raw images to be processed by  applying general operations such as cropping and resizing  the images and applying noise reduction filters, finding  global mean and using it for thresholding and also applying  a pad for distinct borders to avoid confusion. The DR can  be observed at rapid levels simply and destruction of the  retina will be less. The key research methodology is stated  that describing patterns that report the characteristics of an  entire image such as outcome arranged images are graceful  with dissimilar filters, geomorphologic tools, noise  contraction, background separate and vessel separation.  Comparison of ANN technique, and support vector machine  (SVM) technique used for the classification and grading  technique based on supervised learning.
Keywords: Diabetic Retinopathy; DR; SVM; ANN; classification; AMD (Age-related macular degeneration)